Andrographolide Promotes Interaction Between Endothelin-Dependent EDNRA/EDNRB and Myocardin-SRF to Regulate Pathological Vascular Remodeling - Hu, Wangming; Wu, Xiao; Jin, Zhong; Wang, Zheng; Guo, Qiru; Chen, Zixian; Zhu, Song; Zhang, Haidi; Huo, Jian; Zhang, Lingling; Zhou, Xin; Yang, Lan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Pathological vascular remodeling is a hallmark of various vascular diseases. Smooth muscle cell (SMC) phenotypic switching plays a pivotal role during pathological vascular remodeling. The mechanism that how to regulate SMC phenotypic switching is still need to be defined. This study aims to investigate the effect of Andrographolide on pathological vascular remodeling and its underlying mechanism. Methods C57/BL6 mouse left carotid artery complete ligation model and rat SMC were used to determine whether Andrographolide is critical in regulating SMC phenotypic switching. Quantitative real-time PCR, CCK8 cell proliferation assay, BRDU incorporation assay, Boyden chamber migration assay and Spheroid sprouting assay were performed to evaluate whether Andrographolide suppresses proliferation and migration of SMC. Immunohistochemistry staining, Immunofluorescence staining and protein CO-immunoprecipitation were used to observe interaction between EDNRA, EDNRB and Myocardin-SRF. Results Andrographolide inhibits neointimal hyperplasia in left carotid artery complete ligation model. Andrographolide regulates SMC phenotypic switching characterized by suppressing proliferation and migration of SMC. Andrographolide activities Endothelin signaling pathway exhibited by dramatically inducing EDNRA and EDNRB expression. The interaction between EDNRA/EDNRB and Myocardin-SRF resulting in promoting SMC differentiation marker genes expression. Conclusion Andrographolide plays a critical role in regulating pathological vascular remodeling.